RUANG YANG BERBICARA: FUNGSI RUANG TERHADAP PERSEBARAN KOLOM CENDAWAN DI PASAR JATINGALEH - Maulana Ilham; Bangun Harsritanto (Universitas Katolik Soegijapranata, 2026)
Traditional markets are one of the key centers of economic activity in community life, including Jatingaleh Market located in the city of Semarang. In addition to serving as a hub of economic activity, Jatingaleh Market has a unique design feature: the use of mushroom-shaped columns distributed throughout the building. These columns function not only as structural elements but also help form spatial zones that influence the internal spatial layout. Based on this uniqueness, this study aims to understand how the spaces in Jatingaleh Market are formed and function as a result of the distribution of the mushroom columns. The research approach involves examining the market’s spatial organization, identifying the zones that emerge, and analyzing the function of each space in shaping the overall spatial structure. The findings of this study are expected to serve as a foundation for developing traditional market designs that are more functional, comfortable, and responsive to the needs of the community.